M. S. Drinov on Rus’ and Byzantium as Enemies of Bulgaria in the Tenth Century - Domanovska, Marina (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences)
The article deals with M. S. Drinov’s perception and evaluation of the enemies of Bulgaria in the Russo-Byzantine-Bulgarian confrontation of the tenth century. Particular attention is paid to the impact of Drinovʼs personal socio-political views on his interpretation of the Byzantine-Bulgarian war of 966-972 and Prince Sviatoslav’s struggle for supremacy in the Balkans. The author concludes that Drinov treated Byzantium as the enemy of Bulgaria more loyally than Rus’. Byzantine rule, according to Drinov, was able to ensure further development of Bulgarian society via following the best achievements of Byzantine civilization. Submitting to pagan Svyatoslav would have thrown Bulgarians back into the recent barbarity, which they had managed to overcome with the help of Byzantium.